Islamic finance arbitration: integrating the classical and modern legal frameworks - Oseni, Umar Aimhanosi (The Malaysian Current Law Journal Sdn. Bhd., 2016)
With the increasing significance of Islamic financial services in the global financial system, there is a paradigm shift to sustainable dispute resolution practices to secure ongoing business relationship. Legal experts have been exploring how the legal templates, borrowed from the age-long practice in common law jurisdictions, can be applied to legal and enforcement challenges arising out of decisions of the court on Islamic banking and finance services. This has led to the formulation of Shari’ahcompliant procedural rules for the resolution of disputes, in the form of institutionalised Alternative Dispute Resolution (ADR). From a review of the existing rules for arbitration of disputes from Islamic banking and financial services, it is clear that most of the institutional rules are patterned after the UNCITRAL Arbitration Rules 2010,1 with some structural modifications, adaptations and amendments. While there is nothing unusual in modelling the institutional rules for arbitration in Islamic banking and finance based on the UNCITRAL Arbitration Rules, there are certain specific principles that need to be considered in harmonising the classical Islamic principles of commercial dispute resolution with the modern legal framework for arbitration.